A new species of Bryconamericus (Characiformes: Characidae) from the Cuña-Pirú creek in north-eastern Argentina, with comments on accompanying fishes - Miquelarena, Amalia María (2002)
A new species of the characid genus Bryconamericus is described from a tributary of the upper Paraná River, in the province of Misiones, Argentina. The new species can be distinguished from all other species of the genus by the presence of an irregular series of tricuspid teeth on the outer premaxillary row; branched anal fin rays 16-19; perforated scales on lateral line 37-40; a different coloration pattern, with a wide, silvery lateral band and a vertically-elongated humeral spot; very weak sexual dimorphism and the absence of bony hooks on fins in males. A list of fish incidentally collected with the new species is also included.